Bound states in the continuum in double-hole array perforated in a layer of photonic crystal slab. (13th November 2019) - Xie, Suxia; Xie, Changzhong; Xie, Song; Zhan, Jie; Li, Zhijian; Liu, Qiong; Tian, Guang
Abstract: We theoretically investigate optical bound states in the continuum (BIC) supported by a double-hole array. It verifies BICs around 0° can be observed only in the structure with symmetrical nanohole shape in one lattice. At arbitrary oblique incident angles, BIC with Q-factors exceeding 10 6 can be found in the double-hole arrays in both types, which are sensitive to the refractive index of the surrounding medium. Results from both finite-difference time-domain method and temporal coupled mode theory accord well, and they are helpful in the design of novel photonic elements based on BICs, such as sensors, and filters.